Expansão da citricultura no estado de São Paulo (2000 – 2022): novas regiões produtivas e concentração da produção (Revista Brasileira Multidisciplinar, 2025)
This article analyzes the changes that have occurred in the structure of citrus production in the State of São Paulo since the 2000s, when the Citrus Agroindustrial Complex (CAI) expanded globally, gaining new markets, technological self-sufficiency, and greater operational capacity. This is a qualitative and quantitative study, of an exploratory nature, with a historical and descriptive perspective, based on secondary sources, which mapped 20 years of orange production. The study identified the presence of new production regions, the intensive use of technology, changes, and strong land concentration that led to the exclusion of approximately 14,000 small and medium-sized producers without a minimum production scale. It revealed the role of Fundecitrus, which changed its institutional profile with the use of science and technology, contributed to increasing the verticalization of production, and strengthened the capitalist strategy of maintaining the largest and most efficient system for transforming renewable natural resources into financial resources.